Automated systems in the aviation and aerospace industries - Shmelova, Tetiana, 1961-; Sikirda, Yuliya, 1978-; Rizun, Nina, 1968-; Kucherov, Dmytro; Dergachov, Konstantin (Advances in mechatronics and mechanical engineering (AMME) book series., 2019)
"This book explores the use of automated systems in the aviation and aerospace industries. It also examines the challenges and issues surrounding the development of training for automated systems"--